Low-shrinkage ultra-high performance concrete and preparation method thereof

By using phosphogypsum-based crude aggregate and solid waste light aggregate prepared by industrial solid waste in ultra-high performance concrete, combined with homemade expansion agent, the problems of high cost and high shrinkage risk of ultra-high performance concrete are solved, and the problem of high cost and high shrinkage risk is achieved. High strength, low shrinkage and environmentally friendly effects.

CN119490337APending Publication Date: 2025-02-21HUBEI UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411645386.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Ultra-high performance concrete has low water glue, high cost, and high shrinkage risk, which leads to cracking. Its application environment is complex and has high requirements for compressive strength and working performance.

Method used

By replacing cement with a large amount of blends, the production cost of concrete is reduced, and industrial solid waste is used to prepare phosphogypsum-based coarse aggregate and solid waste light aggregate as aggregate, the strength of concrete is improved, and the internal curing effect is exerted, with homemade expansion The agents jointly reduce ultra-high performance concrete shrinkage.

Benefits of technology

The high compressive strength and flexural strength of low-shrinkage ultra-high performance concrete are achieved, which reduces self-shrinkage and drying shrinkage, significantly reduces production costs, and consumes a large amount of industrial solid waste, which has significant environmental and economic benefits.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of cement-based building materials, in particular to low-shrinkage ultra-high-performance concrete and a preparation method thereof.The concrete production cost is reduced by replacing cement with a large amount of admixture, ardealite-based coarse aggregate and solid waste lightweight aggregate are prepared from industrial solid waste to serve as aggregate, and the concrete strength is improved; the internal curing effect is achieved, and the shrinkage of the ultra-high performance concrete is reduced together with a self-made expanding agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based building materials, and in particular to a low-shrinkage ultra-high performance concrete and a preparation method thereof. Background Art

[0002] Ultra-high performance concrete, referred to as UHPC, is a new type of cement-based engineering material with excellent properties such as ultra-high strength, high toughness, high impermeability and high corrosion resistance.

[0003] The excellent performance of UHPC makes its application prospects very broad. It can be used in large-span structures, super-high-rise buildings, tunnels, military protection special projects and other fields.

[0004] However, there are several problems with ultra-high performance concrete. First, ultra-high performance concrete has a relatively low water-cement ratio and a large amount of cement, so its cost is relatively high. Second, ultra-high performance concrete itself will have a large shrinkage, which brings with it the risk of cracking. Third, due to the complex application environment of ultra-high performance concrete, high requirements are placed on its compressive strength and working performance. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a low-shrinkage ultra-high performance concrete, which reduces the cost of concrete production by adopting a large amount of admixtures to replace cement, and utilizes industrial solid waste to prepare phosphogypsum-based coarse aggregate and solid waste lightweight aggregate as aggregate, thereby improving the strength of concrete and exerting an internal curing effect, thereby reducing the shrinkage of ultra-high performance concrete together with a homemade expansion agent.

[0006] Specifically, the low shrinkage ultra-high performance concrete of the present invention is composed of the following raw materials in parts by weight: 550-650 parts of cement, 150-250 parts of silica fume, 100-200 parts of mineral powder, 150-250 parts of fly ash, 40-60 parts of expansion agent, 270-340 parts of phosphogypsum-based coarse aggregate, 800-1000 parts of solid waste lightweight aggregate, 140-160 parts of steel fiber, 20-25 parts of water reducer, 2-5 parts of activator, and 330-380 parts of water.

[0007] The expansion agent preparation process is as follows: limestone, magnesite and fly ash are mixed and ground in a mass ratio of (6-7):(1-3):(1-2), calcined at high temperature, rapidly cooled and ground to obtain the expansion agent.

[0008] The phosphogypsum-based coarse aggregate preparation process comprises: mixing aged phosphogypsum and cement in a mass ratio of 1:(0.8-1.2) to obtain a mixture, spraying water glass on the mixture in a mass ratio of 1:(0.2-0.3) and rolling granulation to obtain 15-20 mm spherical aggregate, curing, and obtaining the mixture.

[0009] The solid waste light aggregate preparation process is as follows: coal gangue powder, lithium slag powder, desulfurized ash, manganese dioxide, and calcium carbonate are mixed evenly in a mass ratio of (8-9):1:(1-2):(0.4-0.5):(0.1-0.3), sprayed with an appropriate amount of water for rolling granulation to obtain 0.15-2.36 mm balls, calcined, and cooled. During the calcination of the solid waste light aggregate, crystalline phases such as mullite are generated to improve the strength of the aggregate. The elements in the lithium slag powder and desulfurized ash can also reduce the sintering temperature and play a fluxing effect. Calcium carbonate and manganese dioxide can improve the pore-forming effect and enhance the internal curing effect.

[0010] The present invention prepares phosphogypsum-based coarse aggregate and solid waste light aggregate, which have high cylinder compressive strength, so the prepared ultra-high performance concrete has high compressive strength, and compared with natural aggregates, the two homemade aggregates and steel fibers can form a better skeleton lap structure, which helps to ensure the flexural strength of ultra-high performance concrete. In addition, the ultra-high performance concrete slurry of the present invention has good workability, high fluidity, and good working performance. The added expansion agent belongs to a calcium-magnesium-silicon composite expansion agent, which is matched with the internal curing effect of the phosphogypsum-based coarse aggregate and the solid waste light aggregate, and improves the utilization efficiency of the expansion agent and the shrinkage compensation effect.

[0011] The self-made expansion agent of the present invention not only has an expansion effect, but also has a high alkalinity, which can simultaneously stimulate the volcanic ash activity of the mineral admixture to form a tight interface transition zone. During the reaction process, the highly active calcium component can provide a sufficient alkaline environment to promote the rapid conversion of active magnesium into magnesium hydroxide and to form a gel with the cementitious material, thereby preventing the residual free magnesium ions from reacting with the alkali aggregate in the later stage to cause the problem of poor volume stability.

[0012] Preferably, the cement is at least one of Portland cement and ordinary Portland cement, and the strength grade is not less than 42.5.

[0013] Preferably, the SiO2 content in the silica ash is greater than 95%, and the specific surface area is not less than 20000m 2 / kg.

[0014] Preferably, the mineral powder is at least one of S95 and S105 grades, with a specific surface area of ​​not less than 400m 2 / kg.

[0015] Preferably, the fly ash is primary fly ash.

[0016] Preferably, during the preparation of the expansion agent, the high temperature calcination temperature is 950-1000° C., the calcination time is 10-15 min, and the particle size is ground to 1-100 μm.

[0017] Preferably, in the process of preparing the phosphogypsum-based coarse aggregate, the aged phosphogypsum is phosphogypsum aged for more than 2 years and has a particle size of less than 75 μm.

[0018] Preferably, in the preparation process of the solid waste lightweight aggregate, the calcination is performed by pre-calcining at 400-500° C. for 30-50 min, and then heating to 1000-1180° C. for calcining for 50-70 min.

[0019] Preferably, the steel fiber is a copper-plated steel fiber with a length of 12-14 mm, a diameter of 0.15-0.20 mm, and a tensile strength greater than 2850 MPa.

[0020] Preferably, the water reducer is a polycarboxylate water reducer.

[0021] Preferably, the activator is at least one of sodium hydroxide and calcium hydroxide.

[0022] The present invention also relates to a method for preparing the low shrinkage ultra-high performance concrete, which specifically comprises the following steps:

[0023] 1) Weigh each raw material by mass,

[0024] 2) Mix the phosphogypsum-based coarse aggregate and the solid waste lightweight aggregate with part of the water and fully pre-wet them to obtain pre-wetted aggregate.

[0025] 3) Mix cement, silica fume, mineral powder, fly ash and expansion agent evenly to obtain powder.

[0026] 4) Mix the water reducer, activator and remaining water evenly to obtain liquid material.

[0027] 5) Mix the pre-wet aggregate, powder and liquid evenly, add steel fiber and stir evenly.

[0028] The low-shrinkage ultra-high performance concrete of the present invention has ultra-high compressive strength and flexural strength, low autogenous shrinkage and drying shrinkage, can consume a large amount of industrial solid waste, and has significant environmental and economic benefits. DETAILED DESCRIPTION

[0029] In order to characterize the technical effect of the present invention, concrete was prepared and its performance was tested. During the test, P·O52.5 cement was selected, S95 grade ore powder was selected, first grade fly ash was selected, polycarboxylate water reducer was selected, and aged phosphogypsum was phosphogypsum aged for more than 2 years with a particle size of less than 75 μm. In the shrinkage value test, "-" represents shrinkage and "+" represents expansion.

[0030] Example 1

[0031] Concrete, characterized in that it is composed of the following raw materials in parts by weight: 600 parts of cement, 150 parts of silica fume, 180 parts of mineral powder, 220 parts of fly ash, 60 parts of expansion agent, 290 parts of phosphogypsum-based coarse aggregate, 980 parts of solid waste lightweight aggregate, 150 parts of steel fiber, 24 parts of water reducer, 3 parts of calcium hydroxide, and 380 parts of water.

[0032] The expansion agent preparation process is as follows: limestone, magnesite and fly ash are mixed and ground in a mass ratio of 6:2:2, calcined at 950°C for 15 minutes, rapidly cooled, and ground to a particle size of 1-100 μm to obtain the expansion agent.

[0033] The phosphogypsum-based coarse aggregate preparation process is as follows: aged phosphogypsum and cement are uniformly mixed at a mass ratio of 1:1 to obtain a mixture, water glass is sprayed on the mixture at a mass ratio of 1:0.2 and rolled to granulate to obtain 15-20 mm spherical aggregates, and then cured to obtain the mixture.

[0034] The solid waste lightweight aggregate preparation process is as follows: coal gangue powder, lithium slag powder, desulfurized ash, manganese dioxide and calcium carbonate are uniformly mixed in a mass ratio of 9:1:1:0.4:0.2, sprayed with a proper amount of water for rolling granulation to obtain 0.15-2.36 mm ball material, pre-burned at 450° C. for 40 minutes, heated to 1150° C. for calcination for 60 minutes, and cooled to obtain the product.

[0035] After testing, the initial expansion of the concrete was 670mm, the compressive strength at 28d was 160.6MPa, the flexural strength at 28d was 25.3MPa, the autogenous shrinkage at 7d was -39με, and the drying shrinkage at 180d was +37με.

[0036] Example 2

[0037] Concrete, characterized in that it is composed of the following raw materials in parts by weight: 620 parts of cement, 200 parts of silica fume, 100 parts of mineral powder, 200 parts of fly ash, 50 parts of expansion agent, 320 parts of phosphogypsum-based coarse aggregate, 900 parts of solid waste lightweight aggregate, 140 parts of steel fiber, 23 parts of water reducer, 4 parts of calcium hydroxide, and 380 parts of water.

[0038] The expansion agent preparation process is as follows: limestone, magnesite and fly ash are mixed and ground in a mass ratio of 7:1:2, calcined at 1000°C for 12 minutes, rapidly cooled, and ground to a particle size of 1-100 μm to obtain the expansion agent.

[0039] The phosphogypsum-based coarse aggregate preparation process is as follows: aged phosphogypsum and cement are uniformly mixed at a mass ratio of 1:1.1 to obtain a mixture, water glass is sprayed on the mixture at a mass ratio of 1:0.3 and granulated by rolling to obtain 15-20 mm spherical aggregates, and then cured to obtain the mixture.

[0040] The solid waste lightweight aggregate preparation process is as follows: coal gangue powder, lithium slag powder, desulfurized ash, manganese dioxide and calcium carbonate are uniformly mixed in a mass ratio of 8:1:2:0.4:0.3), sprayed with an appropriate amount of water for rolling granulation to obtain 0.15-2.36 mm ball material, pre-burned at 500° C. for 35 minutes, heated to 1120° C. for calcination for 60 minutes, and cooled to obtain the material.

[0041] After testing, the initial expansion of the concrete is 650mm, the 28d compressive strength is 157.5MPa, the 28d flexural strength is 23.4MPa, the 7d autogenous shrinkage is -42με, and the 180d drying shrinkage is +34με.

[0042] Comparative Example 1

[0043] Concrete, characterized in that it is composed of the following raw materials in parts by weight: 600 parts of cement, 150 parts of silica fume, 180 parts of mineral powder, 220 parts of fly ash, 60 parts of CSA expansion agent, 290 parts of phosphogypsum-based coarse aggregate, 980 parts of solid waste lightweight aggregate, 150 parts of steel fiber, 24 parts of water reducer, 3 parts of calcium hydroxide, and 380 parts of water.

[0044] The phosphogypsum-based coarse aggregate preparation process is as follows: aged phosphogypsum and cement are uniformly mixed at a mass ratio of 1:1 to obtain a mixture, water glass is sprayed on the mixture at a mass ratio of 1:0.2 and rolled to granulate to obtain 15-20 mm spherical aggregates, and then cured to obtain the mixture.

[0045] The solid waste lightweight aggregate preparation process is as follows: coal gangue powder, lithium slag powder, desulfurized ash, manganese dioxide and calcium carbonate are uniformly mixed in a mass ratio of 9:1:1:0.4:0.2, sprayed with a proper amount of water for rolling granulation to obtain 0.15-2.36 mm ball material, pre-burned at 450° C. for 40 minutes, heated to 1150° C. for calcination for 60 minutes, and cooled to obtain the product.

[0046] After testing, the initial expansion of the concrete was 630mm, the 28d compressive strength was 146.4MPa, the 28d flexural strength was 19.1MPa, the 7d autogenous shrinkage was -56με, and the 180d drying shrinkage was -13με.

[0047] Comparative Example 2

[0048] Concrete, characterized in that it is composed of the following raw materials in parts by weight: 600 parts of cement, 150 parts of silica fume, 180 parts of mineral powder, 220 parts of fly ash, 60 parts of expansion agent, 290 parts of 15-20 mm crushed stone, 980 parts of solid waste lightweight aggregate, 150 parts of steel fiber, 24 parts of water reducer, 3 parts of calcium hydroxide, and 380 parts of water.

[0049] The expansion agent preparation process is as follows: limestone, magnesite and fly ash are mixed and ground in a mass ratio of 6:2:2, calcined at 950°C for 15 minutes, rapidly cooled, and ground to a particle size of 1-100 μm to obtain the expansion agent.

[0050] The solid waste lightweight aggregate preparation process is as follows: coal gangue powder, lithium slag powder, desulfurized ash, manganese dioxide and calcium carbonate are uniformly mixed in a mass ratio of 9:1:1:0.4:0.2, sprayed with a proper amount of water for rolling granulation to obtain 0.15-2.36 mm ball material, pre-burned at 450° C. for 40 minutes, heated to 1150° C. for calcination for 60 minutes, and cooled to obtain the product.

[0051] After testing, the initial expansion of the concrete was 600mm, the 28d compressive strength was 127.0MPa, the 28d flexural strength was 16.7MPa, the 7d autogenous shrinkage was -107με, and the 180d drying shrinkage was -98με.

[0052] Comparative Example 3

[0053] Concrete, characterized in that it is composed of the following raw materials in parts by weight: 600 parts of cement, 150 parts of silica fume, 180 parts of mineral powder, 220 parts of fly ash, 60 parts of expansion agent, 290 parts of phosphogypsum-based coarse aggregate, 980 parts of solid waste lightweight aggregate, 150 parts of steel fiber, 24 parts of water reducer, 3 parts of calcium hydroxide, and 380 parts of water.

[0054] The expansion agent preparation process is as follows: limestone and magnesite are mixed and ground in a mass ratio of 6:2, calcined at 950°C for 15 minutes, rapidly cooled, and ground to a particle size of 1-100 μm to obtain the expansion agent.

[0055] The phosphogypsum-based coarse aggregate preparation process is as follows: phosphogypsum and cement are uniformly mixed at a mass ratio of 1:1 to obtain a mixture, water glass is sprayed on the mixture at a mass ratio of 1:0.2 and rolled to granulate to obtain 15-20 mm spherical aggregates, and curing is performed to obtain the mixture.

[0056] The solid waste lightweight aggregate preparation process is as follows: coal gangue powder, lithium slag powder, desulfurized ash, manganese dioxide and calcium carbonate are uniformly mixed in a mass ratio of 9:1:1:0.4:0.2, sprayed with a proper amount of water for rolling granulation to obtain 0.15-2.36 mm ball material, pre-burned at 450° C. for 40 minutes, heated to 1150° C. for calcination for 60 minutes, and cooled to obtain the product.

[0057] After testing, the initial expansion of the concrete was 620mm, the 28d compressive strength was 149.0MPa, the 28d flexural strength was 20.6MPa, the 7d autogenous shrinkage was -118με, and the 180d drying shrinkage was -34με.

[0058] Comparative Example 4

[0059] Concrete, characterized in that it is composed of the following raw materials in parts by weight: 600 parts of cement, 150 parts of silica fume, 180 parts of mineral powder, 220 parts of fly ash, 60 parts of expansion agent, 290 parts of phosphogypsum-based coarse aggregate, 980 parts of river sand, 150 parts of steel fiber, 24 parts of water reducer, 3 parts of calcium hydroxide, and 380 parts of water.

[0060] The expansion agent preparation process is as follows: limestone, magnesite and mineral powder are mixed and ground in a mass ratio of 6:2:2, calcined at 950°C for 15 minutes, rapidly cooled, and ground to a particle size of 1-100 μm to obtain the expansion agent.

[0061] The preparation process of the phosphogypsum-based coarse aggregate is as follows: aged phosphogypsum and cement are uniformly mixed in a mass ratio of 1:1 to obtain a mixture, water glass is sprayed on the mixture in a mass ratio of 1:0.2 and granulated by rolling to obtain 15-20 mm spherical aggregates, and the mixture is cured.

[0062] After testing, the initial expansion of concrete is 650mm, the 28d compressive strength is 107.9MPa, the 28d flexural strength is 11.6MPa, the 7d autogenous shrinkage is -304με, and the 180d drying shrinkage is -178με.

[0063] Comparative Example 5

[0064] Concrete, characterized in that it is composed of the following raw materials in parts by weight: 600 parts of cement, 150 parts of silica fume, 180 parts of mineral powder, 220 parts of fly ash, 60 parts of expansion agent, 290 parts of phosphogypsum-based coarse aggregate, 980 parts of solid waste lightweight aggregate, 150 parts of steel fiber, 24 parts of water reducer, 3 parts of calcium hydroxide, and 380 parts of water.

[0065] The expansion agent preparation process is as follows: limestone, magnesite and fly ash are mixed and ground in a mass ratio of 6:2:2, calcined at 950°C for 15 minutes, rapidly cooled, and ground to a particle size of 1-100 μm to obtain the expansion agent.

[0066] The phosphogypsum-based coarse aggregate preparation process is as follows: aged phosphogypsum and cement are uniformly mixed at a mass ratio of 1:1 to obtain a mixture, water glass is sprayed on the mixture at a mass ratio of 1:0.2 and rolled to granulate to obtain 15-20 mm spherical aggregates, and then cured to obtain the mixture.

[0067] The solid waste lightweight aggregate preparation process is as follows: coal gangue powder, slag powder, fly ash, manganese dioxide and calcium carbonate are uniformly mixed in a mass ratio of 9:1:1:0.4:0.2, sprayed with a proper amount of water for rolling granulation to obtain 0.15-2.36 mm ball material, pre-burned at 450° C. for 40 minutes, heated to 1150° C. for calcination for 60 minutes, and cooled to obtain the product.

[0068] After testing, the initial expansion of the concrete was 650mm, the 28d compressive strength was 131.7MPa, the 28d flexural strength was 10.1MPa, the 7d autogenous shrinkage was -185με, and the 180d drying shrinkage was -52με.

[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A low shrinkage ultra-high performance concrete, characterized in that: It is composed of the following raw materials in parts by weight: 550-650 parts of cement, 150-250 parts of silica fume, 100-200 parts of mineral powder, 150-250 parts of fly ash, 40-60 parts of expansion agent, 270-340 parts of phosphogypsum-based coarse aggregate, 800-1000 parts of solid waste lightweight aggregate, 140-160 parts of steel fiber, 20-25 parts of water reducer, 2-5 parts of activator, and 330-380 parts of water. The expansion agent preparation process is as follows: limestone, magnesite and fly ash are mixed and ground in a mass ratio of (6-7):(1-3):(1-2), calcined at high temperature, rapidly cooled and ground to obtain the expansion agent. The phosphogypsum-based coarse aggregate preparation process comprises: mixing aged phosphogypsum and cement in a mass ratio of 1:(0.8-1.2) to obtain a mixture, spraying water glass on the mixture in a mass ratio of 1:(0.2-0.3) and rolling granulation to obtain 15-20 mm spherical aggregate, curing, and obtaining the mixture. The solid waste lightweight aggregate preparation process is as follows: coal gangue powder, lithium slag powder, desulfurized ash, manganese dioxide and calcium carbonate are uniformly mixed in a mass ratio of (8-9):1:(1-2):(0.4-0.5):(0.1-0.3), sprayed with a proper amount of water for rolling granulation to obtain 0.15-2.36 mm ball material, calcined, and cooled to obtain the product.

2. The low shrinkage ultra-high performance concrete according to claim 1, characterized in that: The cement is at least one of silicate cement and ordinary silicate cement, and the strength grade is not less than 42.

5.

3. The low shrinkage ultra-high performance concrete according to claim 1, characterized in that: The SiO2 content in the silica ash is greater than 95%, and the specific surface area is not less than 20000m 2 / kg.

4. The low shrinkage ultra-high performance concrete according to claim 1, characterized in that: The mineral powder is at least one of S95 and S105 grades, with a specific surface area of ​​not less than 400m 2 / kg.

5. The low shrinkage ultra-high performance concrete according to claim 1, characterized in that: The fly ash is primary fly ash.

6. The low shrinkage ultra-high performance concrete according to claim 1, characterized in that: During the preparation of the expansion agent, the high temperature calcination temperature is 950-1000° C., the calcination time is 10-15 minutes, and the particle size is ground to 1-100 μm.

7. The low shrinkage ultra-high performance concrete according to claim 1, characterized in that: In the preparation process of the phosphogypsum-based coarse aggregate, the aged phosphogypsum is phosphogypsum aged for more than 2 years and has a particle size of less than 75 μm.

8. The low shrinkage ultra-high performance concrete according to claim 1, characterized in that: In the preparation process of the solid waste lightweight aggregate, the calcination is performed by pre-calcining at 400-500° C. for 30-50 minutes, and then heating to 1000-1180° C. for calcining for 50-70 minutes.

9. The low shrinkage ultra-high performance concrete according to claim 1, characterized in that: The activator is at least one of sodium hydroxide and calcium hydroxide.

10. The method for preparing low shrinkage ultra-high performance concrete according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh each raw material by mass. 2) Mix the phosphogypsum-based coarse aggregate and the solid waste lightweight aggregate with part of the water and fully pre-wet them to obtain pre-wetted aggregate. 3) Mix cement, silica fume, mineral powder, fly ash and expansion agent evenly to obtain powder. 4) Mix the water reducer, activator and remaining water evenly to obtain liquid material. 5) Mix the pre-wet aggregate, powder and liquid evenly, add steel fiber and stir evenly.

Citation Information

Cited By

  • Low-shrinkage concrete block and preparation method thereof

    CN119797867A

  • Low-shrinkage high-crack-resistance ultra-high performance concrete and preparation method thereof

    CN120903881A